2021
DOI: 10.3389/fneur.2021.747878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes on Post-stroke Recovery: A Systematic Narrative Review

Abstract: Background: Patients with stroke often have comorbid diabetes. Considering its detrimental effects on brain function, diabetes may increase the risk of poor recovery.Methods: The aim of this review was to investigate the effect of diabetes on post-stroke recovery by a systematic review. Several specific aspects of post-stroke recovery, including activities of daily living (ADL), motor, cognitive, and quality of life (QOL) recovery, were examined. We searched the PubMed, SCOPUS, Embase, and Cochrane Library dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…In addition, up to half of stroke survivors and individuals with T2DM experience fatigue ( 7 , 8 ) and/or depression ( 9 , 10 ). Added up these factors make this group particularly vulnerable, prone to sedentary behavior (SB) ( 11 , 12 ), poor ability to perform activities of daily living (ADL) ( 13 ), and low quality of life (QoL) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, up to half of stroke survivors and individuals with T2DM experience fatigue ( 7 , 8 ) and/or depression ( 9 , 10 ). Added up these factors make this group particularly vulnerable, prone to sedentary behavior (SB) ( 11 , 12 ), poor ability to perform activities of daily living (ADL) ( 13 ), and low quality of life (QoL) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…This theory has previously been used in co-creation processes ( 22 , 26 , 27 ) but co-creation frameworks have not been applied for a population of stroke survivors with T2DM ( 28 ). However, co-creation may be a feasible way to obtain a better understanding of SB and PA behaviors in this population as T2DM, SB and low levels of PA increase the risk of stroke ( 5 , 6 , 14 ), poor post-stroke recovery ( 13 , 42 ), morbidity, and mortality ( 18 , 19 ). Therefore, interventions that aim for beneficial effects of PA in stroke survivors with T2DM are desirable ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…T2D is a strong risk factor for stroke [ 2 ] and the leading cause of mortality from cardiovascular disease [ 3 ]. T2D also worsens stroke recovery [ 4 ] and increases the disability burden, being a strong predictor of post-stroke dependency on assistive care [ 5 , 6 , 7 , 8 ]. Despite the availability of pharmacological and lifestyle change strategies that reduce stroke risk in T2D [ 3 ], efficacious therapies to improve post-stroke recovery and reduce stroke sequelae in this group of people are entirely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to recognize the related markers and factors associated with poststroke results in arrange to direct clinical stroke administration way better. Emerging evidence suggested that metabolic related factors, such as obesity, insulin resistance, type 2 diabetes mellitus, have a great implication for stroke incidence as well as its prognosis (Lau et al., 2019; Rodríguez‐Castro et al., 2019; Yang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggested that metabolic related factors, such as obesity, insulin resistance, type 2 diabetes mellitus, have a great implication for stroke incidence as well as its prognosis (Lau et al, 2019;Rodríguez-Castro et al, 2019;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%